Impact of operatoŕs experience on peri-procedural outcomes with Watchman FLX: Insights from the FLX-SPA registry. (February 2022) - Cruz-González, Ignacio; Torres Saura, Francisco; Trejo-Velasco, Blanca; Antonio Fernández Díaz, José; Fajardo Molina, Ricardo; del Valle-Fernández, Raquel; Moreno Terribas, Gerardo; Martí Sánchez, David; López-Mínguez, José-Ramón; Gomez-Blazquez, Ivan; Sanmartin Pena, Juan-Carlos; Botas, Javier; et al.
Abstract: Background: The Watchman FLX is a device upgrade of the Watchman 2.5 that incorporates several design enhancements intended to simplify left atrial appendage occlusion (LAAO) and improve procedural outcomes. This study compares peri -procedural results of LAAO with Watchman FLX (Boston Scientific, Marlborough, Massachusetts) in centers with varying degrees of experience with the Watchman 2.5 and Watchman FLX. Methods: Prospective, multicenter, "real-world" registry including consecutive patients undergoing LAAO with the Watchman FLX at 26 Spanish sites (FLX-SPA registry). Implanting centers were classified according to the center's prior experience with the Watchman 2.5. A further division of centers according to whether or not they had performed ≤ 10 or > 10Watchman FLX implants was prespecified at the beginning of the study. Procedural outcomes of institutions stratified according to their experience with the Watchman 2.5 and FLX devices were compared. Results: 359 patients [mean age 75.5 (SD8.1), CHA2 DS2 -VASc 4.4 (SD1.4), HAS-BLED 3.8(SD0.9)] were included. Global success rate was 98.6%, successful LAAO with the first selected device size was achieved in 95.5% patients and the device was implanted at first attempt in 78.6% cases. There were only 9(2.5%) major peri -procedural complications. No differences in efficacy or safety results according to the centeŕs previous experience with Watchman 2.5 and procedural volume with Watchman FLX existed. Conclusions: The Watchman FLX attains high procedural success rates with complete LAA sealing in unselected, real-world patients, along with a low incidence of peri -procedural complications, regardless of operatoŕs experience with its previous device iteration or the number of Watchman FLX devices implanted.